The Planning and Design Characteristics of the Integrated Master Plan for Urban and Architecture in 3rd Generation New Towns-In Case of Gwacheon Gwacheon, Ansan Singil 2 and Suwon Dangsu 2 - Han, Ji Houng (Journal of the Architectural Institute of Korea, 2023)
This study aims to analyze the master plans of winning proposals from design competitions related to 3rd generation new towns, particularly three pilot districts: Gwacheon Gwacheon District, Suwon Dangsu District 2 and Ansan Singil District 2. The concept and principles of the integrated urban and architectural planning were applied for the first time to grasp the meaning and seek improvement direction for planning and design standards. Based on basic principles and directions of the design guidelines presented at the time of these competitions, how they were interpreted and what solutions were presented was analyzed; the characteristics of the three-dimensional urban space planning of each district was compared, commonalities and differences were examined, and implications were derived. To further analyze the detailed planning elements and characteristics, the planning and design criteria according to the spatial hierarchy of the integrated urban and architectural planning regarding region or city scale, district or neighborhood scale, and block, street or building scale were applied to the three pilot districts. The planning and design solutions from the plan's vision and goals to the architectural design direction were compared and analyzed. Lastly, the synthesis and significance of the analysis results, the improvement direction of the plans and design standards during the master plan competitions, and future tasks for the realization of an integrated urban and architectural planning were summarized and presented.
Keywords: 3rd Generation New Towns; Integrated Urban & Architectural Planning; Master Plan; Planning and Design Criteria; Three-dimensional Urban Space